The Association Between Negative and Positive Affect and Alcohol Use: An Ambulatory Study - Bresin, Konrad (J Stud Alcohol Drugs, 2019)
OBJECTIVE: Negative and positive affect are proposed to play a crucial role in alcohol use and the development of alcohol use disorder. Results from ambulatory studies that measure momentary affect and subsequent alcohol use have been mixed, particularly regarding negative affect. We attempted to identify within-person moderators (i.e., time between assessments, prior blood alcohol content) that might explain mixed results. METHOD: We examined the association between self-reported affect and an objective measure of alcohol consumption (measured via a transdermal ankle bracelet) in a sample of heavy social drinkers across 7 days of ambulatory assessment. RESULTS: Our results showed that negative affect was negatively related to later drinking, whereas positive affect was positively related to later drinking. The results showed that these effects were stronger for amount consumed when affect was assessed closer rather than farther in time. CONCLUSIONS: These findings are important for understanding affect as an antecedent to alcohol use, which may ultimately have implications for the development of alcohol use disorder.